a, \(\dfrac{n^2+5}{n+3}=\dfrac{n^2+3n-3n-9+14}{n+3}=\dfrac{\left(n+3\right).\left(n-3\right)+14}{n+3}\)
\(=\dfrac{\left(n+3\right)\left(n-3\right)}{n+3}+\dfrac{14}{n+3}=n-3+\dfrac{14}{n+3}\)
Để \(\dfrac{n^2+5}{n+3}\) đạt giá trị nguyên thì \(\dfrac{14}{n+3}\) đạt giá trị nguyên.
\(\Rightarrow n+3\inƯ\left(14\right)\)
\(\Rightarrow n+3\in\left\{-14;-7;-2;-1;1;2;7;14\right\}\)
\(\Rightarrow n\in\left\{-17;-10;-5;-4;-2;-1;4;11\right\}\)
mà \(n\in N\Rightarrow n\in\left\{4;11\right\}\)
Vậy......
Câu b,c tương tự
Chúc bạn học tốt!!!